Critical Role of TLR2 and MyD88 for Functional Response of Macrophages to a Group IIA-Secreted Phospholipase A2 from Snake Venom - Leiguez, Elbio (2014)
artículo (arbitrado) -- Universidad de Costa Rica, Instituto de Investigaciones Clodomiro Picado. 2014